Plasma Epstein-Barr Virus-Deoxyribonucleic Acid Copy Number Predicts Disease Progression in Stage I–III Pulmonary Lymphoepithelioma-Like Carcinoma - Li, Qi-Wen; Qiu, Bo; Hu, Wan-Ming; Guo, Su-Ping; Wu, Ying-Jia; Zhu, Yu-Jia; Hu, Nan; Ai, Xin-Lei; Chen, Nai-Bin; Guo, Jin-Yu; Hu, Yong-Hong; Liu, Meng-Zhong; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate the predictive values of plasma Epstein-Barr Virus (EBV)- deoxyribonucleic acid (DNA) copy number on disease progression and survival in stage I-III pulmonary lymphoepithelioma-like carcinoma (LELC). Patients and Methods: Patients with pathologically confirmed, initially diagnosed or locally recurrent stage I-III pulmonary LELC, who received locally radical treatment and had plasma EBV-DNA results, were retrospectively reviewed. Risk factors of progression-free survival (PFS) and overall survival (OS) were assessed, including the predictive value of pre- and post-treatment EBV-DNA levels. The EBV-DNA change during follow-up was analyzed to determine its association with tumor progression. Results: A total of 102 patients were included in analysis. Eighty-eight patients had initially-diagnosed and 14 had locally recurrent disease. There were 33 patients treated with radical surgery, 55 with definite radiotherapy and 14 with both. EBV-DNA was tested pre-treatment (N=66), post-treatment (N=93) and/or during follow-up (N=58). The overall 2-year PFS and OS were 65.9% (95% CI, 56.1-75.7%) and 95.9% (95% CI, 91.4-100.4%), respectively. Pre-treatment EBV-DNA copy number >10000 copies/mL was a risk factor of PFS (2-year PFS, >10000 vs ≤10000 copies/mL, 37.2% vs 75.1%, p=0.007). Positive post-treatment EBV-DNA also indicated a worse PFS in univariable (2-year PFS, >0 vs 0 copy/mL, 25.6% vs 76.8%, p<0.001) and multivariable analysis (HR=3.44, 95% CI, 1.52-7.78; p=0.003). In the follow-up set, an increaseing EBV-DNA exceeding 1000 copies/mL strongly predicted disease progression within 3 months, with a specificity of 97.5% (95% CI: 86.8-99.6%). Conclusions: Regular testing of EBV-DNA is suggested for pulmonary LELC to predict disease progression. If EBV-DNA copy number was increasing and beyond 1000 copies/mL during follow-up, intensive radiologic evaluations are recommended.